2017
DOI: 10.1016/j.str.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Analysis of the C-Terminal Region of FliG, an Essential Motor Component of Vibrio Na+-Driven Flagella

Abstract: The flagellar motor protein complex consists of rotor and stator proteins. Their interaction generates torque of flagellum, which rotates bidirectionally, clockwise (CW) and counterclockwise. FliG, one of the rotor proteins, consists of three domains: N-terminal (FliG), middle (FliG), and C-terminal (FliG). We have identified point mutations in FliG from Vibrio alginolyticus, which affect the flagellar motility. To understand the molecular mechanisms, we explored the structural and dynamic properties of FliG f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…A hinge connecting FliG CN and FliG CC has a highly flexible nature at the conserved MFXF motif, allowing FliG CC to rotate 180° relative to FliG CN to reorient Arg-281 and Asp-289 residues in Helix Torque to achieve a symmetric elementary process of torque generation in both CCW and CW rotation ( Fig. 3 B) [ [53] , [54] , [55] , [56] ]. Structural comparisons between Tm-FliG MC of the wild-type and Tm-FliG MC with the CW-locked deletion have shown that the CW-locked deletion induces a 90° rotation of FliG CC relative to FliG CN through the MFXF motif ( Fig.…”
Section: Structural Basis For the Rotational Switching Mechanismmentioning
confidence: 99%
“…A hinge connecting FliG CN and FliG CC has a highly flexible nature at the conserved MFXF motif, allowing FliG CC to rotate 180° relative to FliG CN to reorient Arg-281 and Asp-289 residues in Helix Torque to achieve a symmetric elementary process of torque generation in both CCW and CW rotation ( Fig. 3 B) [ [53] , [54] , [55] , [56] ]. Structural comparisons between Tm-FliG MC of the wild-type and Tm-FliG MC with the CW-locked deletion have shown that the CW-locked deletion induces a 90° rotation of FliG CC relative to FliG CN through the MFXF motif ( Fig.…”
Section: Structural Basis For the Rotational Switching Mechanismmentioning
confidence: 99%
“…FliG CC is responsible for the interaction with MotA for flagellar motor rotation (Zhou et al., ). Because the elementary process of torque generation by stator–rotor interactions is symmetric in the CCW and CW rotation (Nakamura, Kami‐ike, Yokota, Minamino, & Namba, ), FliG CC is postulated to go through a 180º rotation through a flexible hinge connecting FliG CN and FliG CC when the motor switches between the CCW and CW rotational states of the FliG ring (Lam et al., ; Minamino et al., ; Miyanoiri et al., ; Pandini, Morcos, & Khan, ). Therefore, there is the possibility that the swing motion of Helix MC induced by the binding of CheY‐P to FliM could promote the 180º rotation of FliG CC relative to FliG CN through a conformational change of the hinge between FliG CN and FliG CC .…”
Section: Discussionmentioning
confidence: 99%
“…The C ring acts as a structural switch of the direction of flagellar motor rotation (Morimoto & Minamino, ). CheY‐phosphate (CheY‐P), which acts as a signaling protein responsible for chemotaxis, binds to FliM and FliN to induce highly cooperative remodeling of the FliG ring structure, allowing the motor to spin in the CW direction (Lam et al., ; Lee et al., ; Minamino et al., ; Miyanoiri et al., ). A constitutively active CheY mutant protein of Thermotoga maritima ( Tm‐ CheY*) binds to the T. maritima FliG MC /FliM M complex in solution through an interaction between Tm‐ CheY* and Tm‐ FliM M , thereby disrupting higher‐order oligomer formation of Tm‐ FliG MC that is primarily mediated by intermolecular interactions of Tm‐ FliG CN with Tm‐ FliG M of a neighboring Tm‐ FliG MC subunit (Sircar et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The side chain of K284A cannot be hydrogen‐bonded to the main chain and alters the conformation required for CCW rotation, resulting in reduced torque generation in the CCW direction. Furthermore, we recently found that CW‐biased rotation of a mutant of FliG, A282T, is caused by an additional hydrogen‐bond to the main chain in the C‐terminal domain of FliG (Miyanoiri et al., ). This result also implies that intramolecular interaction in FliG is important for rotational function.…”
Section: Discussionmentioning
confidence: 99%